Religious Attraction and Its Discontents: Tensions Surrounding the Monachization of Baptized Jews in Early Modern Italy - Herzig, Tamar (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
Both female monasticism and Jewish conversion acquired an accentuated significance in Catholic Europe during the age of reformations. Their convergence was ritually expressed in the celebration of the monastic vestition of converts from Judaism. This article centres on the experiences of baptized Jewish girls who entered monastic communities, based on an analysis of cases from central and northern Italy. It argues that Church authorities valued the radical break of formerly Jewish girls with the religious traditions of their ancestors. Yet at the same time, the highly esteemed attraction to female monasticism on the part of baptized Jews could also arouse considerable anxiety, which led to distancing attempts. These, the article suggests, were manifested by restricting converts’ monastic professions to designated institutions; by giving the cold shoulder to baptized Jews who took the veil and socially isolating them within their communities; or by not assisting sickly neophytes to fulfill their religious vocations.